Perbandingan Efek Dilusi pada Nilai Waran dengan Menggunakan Metode Black-Scholes, Dilusi Black-Scholes, dan Pengamatan Variabel - Benny Yong (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2016)
Warrant is a financial derivative product issued by a firm on its own equity. Warrant is different from call options because the exercise price is paid to the firm and increases its assets and new shares of stock are issued at exercise. In this paper, warrant pricing is obtained using three methods; Black-Scholes, diluted Black-Scholes, and observable variables. Specifically, effect of dilution of warrant pricing would be compared each other with different characteristics of contract.Keywords: warrant, dilution, Black-Scholes, diluted Black-Scholes, observable variables